KARAKTERISTIK SEMEN SEGAR SAPI BANGSA LIMOUSIN DAN SIMMENTAL DI BALAI INSEMINASI BUATAN LEMBANG - Muada, Denilisvanti B.; Paputungan, Umar; Hendrik, Manopo J.; Turangan, Santie H. (ZOOTEC, 2017)
FRESH SEMEN CHARACTERISTICS OF LIMOUSIN AND SIMMENTAL BULLS AT THE ARTIFISIAL INSEMINATION CENTER, LEMBANG. This study was conducted to evaluate the characteristics of fresh semen in Limousin and Simmental bulls at the artificial insemination center in Lembang. Results of this study showed that ejaculation frequency of Simmental bull was significantly higher than that of Limousin with the average of 5.37 and 4.60, respectively. Variables of volume, pH and motility were not significantly different between both bulls with volume ranging of 7.17 – 7.20 ml, pH ranging of 6.65 – 6.66 and motility ranging of 58.08 – 59.29%, respectively. The fresh semen colour of Limousin and Simmental bulls were indicated by dominant color of milk white color. Semen consistency of fresh semen from both bulls was moderate. The ejaculation frequency and pH variables indicated the correlation of -0.32 in Limousine bulls, meaning that the higher the ejaculation frequency, the lower the pH  (acid), but the ejaculation frequency and motility of semen had the correlation of 0,34, indicating the more the semen ejaculation frequency, the higher the motility of spermatozoa. The motility of semen had the negative correlation with pH (-0.49). The higher the pH (base), the motility of spermatozoa tended to decline. Simmental bull showed also that semen ejaculation frequency with volume had correlation of -0.40, indicating that the higher the semen ejaculation frequency yakni, the lower the semen volume. Semen ejaculation frequency had correlation of 0.5 with mortality, indicating that the higher the semen ejaculation frequency, the higher the motility of spermatozoa.Keywords: Semen, ejaculation, volume, color, consistency, pH, motility